2009
DOI: 10.1021/jf900964e
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure−Activity Relationship of Botanical Sesquiterpenes: Spatial and Contact Repellency to the Yellow Fever Mosquito, Aedes aegypti

Abstract: The plant terpenoids encompass a diversity of structures and have many functional roles in nature, including protection against pest arthropods. Previous studies in this laboratory have identified naturally occurring sesquiterpenes contained in essential oils from two plants, amyris (Amyris balsamifera) and Siam-wood (Fokienia hodginsii), that are significantly repellent to a spectrum of arthropod pests. In efforts to further examine the biological activity of this class of compounds 12 of these plant-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 37 publications
2
62
0
1
Order By: Relevance
“…For example 360 nmol/cm 2 was the concentration used for QSAR studies of sesquiterpenoid mosquito repellents (Paluch et al 2009). Also for QSAR studies, synthetic mosquito repellents were tested at 2.5 and 25 lmol/cm 2 (Katritzky et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example 360 nmol/cm 2 was the concentration used for QSAR studies of sesquiterpenoid mosquito repellents (Paluch et al 2009). Also for QSAR studies, synthetic mosquito repellents were tested at 2.5 and 25 lmol/cm 2 (Katritzky et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…But, recently QSAR (quantitative structure activity relationships) approaches have been evaluated for discovery of new mosquito repellents, at least repellents having longer durability (Katritzky et al 2008). Also QSAR has been used to provide a better understanding between structure of natural products and their ability to repel mosquitoes (Paluch et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Some terpenoids repel or kill various arthropod pests and have also been implicated in the attraction of pollinators and other beneficial species. For example, some extracts from amyris (Amyris balsamifera) and Siamwood (Fokienia hodginsii) have been implicated in the repellency of mosquito species, while volatiles from Brassica oleracea have been implicated in the attraction of various parasitoids that prey on caterpillars that damage the plants (Paluch et al 2009, Maia and Moore 2011, Poelman et al 2012, Harrewijn et al 1994. While the chemistry of many plant essential oils has been well documented, there is still much to learn about their respective bioactivities, particularly in regards to repellent or lethal activity against insects.…”
mentioning
confidence: 99%
“…The concentrations at which elemol and amyris essential oil repelled I. scapularis and A. americanum in our bioassays and the concentrations which Paluch et al (2009) found repelled A. aegypti mosquitoes are low enough to indicate that elemol and amyris oil should be investigated more thoroughly for their potential as marketable repellents. …”
Section: Discussionmentioning
confidence: 75%